CMV Pancreatitis in an Immunocompromised Patient - Jaffer Ahmad; Najia Sayedy; Raghavendra Sanivarapu; Jagadish Akella; Javed Iqbal (Case Reports in Critical Care)
Introduction. Cytomegalovirus (CMV) is a common double-stranded DNA (dsDNA) virus affecting a large majority of the world’s population. In immunocompetent patients, CMV infection can range anywhere from an asymptomatic course to mononucleosis. However, in the immunocompromised patient, prognosis can be deadly as CMV can disseminate to the retina, liver, lungs, heart, and GI tract. We present a case of CMV pancreatitis afflicting an immunocompromised patient. Case Summary. A 45-year-old Hispanic female with no past medical history presented to the emergency department (ED) for three days of abdominal pain associated with nausea, vomiting, and diarrhea. ED vitals showed a sepsis picture with fever, tachycardia, low white blood cell (WBC) count with bandemia, and CT scan showing acute pancreatitis, cholelithiasis, gastritis, and colitis. The patient denied alcohol use and MRCP showed no stone impaction. Sepsis protocolled was initiated for biliary pancreatitis, and the patient was admitted to the medicine floors with appropriate consulting services. Over the course of admission, the patient responded poorly to treatment and had a steady decline in respiratory status. She tested positive for HIV with a severely depressed CD4 count (42 cells/McL) and high viral load (1,492,761 copies/ml) and started on appropriate prophylactic antibiotics and HAART therapy. The patient was moved to the Medical Intensive Care Unit (MICU) after acute respiratory failure secondary to ARDS requiring mechanical ventilation with initiation of ARDS protocol. The patient was hemodynamically unstable and required vasopressor support. Hospital course was complicated by melena which prompted an esophagogastroduodenostomy (EGD) with biopsy yielding CMV gastritis. Serum CMV viral load was also found to be positive along with an elevated lipase level, indicative of pancreatitis. Despite initiation of ganciclovir, the patient continued to have refractory hypoxia despite full ventilatory support and proning. Unfortunately, the patient was deemed too unstable for transfer to an ECMO facility. She eventually succumbed to respiratory failure. Discussion. CMV is a Herpesviridae virus that is prevalent among more than half of the world’s population. Its effects range from no presenting symptoms to respiratory failure depending on immune status. CMV more commonly affects the retina, lungs, liver, and GI tract; however, in rare cases, it is known to affect the pancreas as well. Other more common causes of pancreatitis were ruled out during the progression of this patient, and an elevated lipase with high CMV viral load points towards CMV pancreatitis. Conclusion. This is one of only a few reported cases of CMV pancreatitis and warrants further study due to the massive prevalence of CMV in the entire world’s population. Our case demonstrates the extent of dissemination of CMV in a severely immunocompromised patient by showing clear cut pancreatitis secondary to said viral infection with exclusion of other possible causes. Our hope is that clinicians will change their practice to include a more scrutinized study into causes of pancreatitis especially in their immunocompromised patients.